Synovial fibroblasts selectively suppress Th1 cell responses through IDO1-mediated tryptophan catabolism - Tykocinski, Lars-Oliver; Lauffer, Anna Marie; Bohnen, Antonia; Kaul, Nathalie-Christin; Krienke, Stefan; Tretter, Theresa; Adam, Isabell; Oezen, Iris; Platten, Michael; Opitz, Christiane; Lorenz, Hanns-Martin (The journal of immunology, 2017)
The development of rheumatoid arthritis (RA) is linked to functional changes in synovial fibroblasts (SF) and local infiltration of T lymphocytes. Fibroblasts possess the capacity to suppress T cell responses, although the molecular mechanisms of this suppression remain incompletely understood. In this study, we aimed to define the mechanisms by which noninflammatory SF modulate Th cell responses and to determine the immunosuppressive efficacy of RASF. Hence, the influence of SF from osteoarthritis or RA patients on total Th cells or different Th cell subsets of healthy donors was analyzed in vitro. We show that SF strongly suppressed the proliferation of Th cells and the secretion of IFN-γ in a cell contact-independent manner. In cocultures of SF and Th cells, tryptophan was completely depleted within a few days, resulting in eukaryotic initiation factor 2α phosphorylation, TCRζ-chain downregulation, and proliferation arrest. Blocking IDO1 activity completely restored Th cell proliferation, but not IFN-γ production. Interestingly, only the proliferation of Th1 cells, but not of Th2 or Th17 cells, was affected. Finally, RASF had a significantly lower IDO1 expression and a weaker Th cell suppressive capacity compared with osteoarthritis SF. We postulate that the suppression of Th cell growth by SF through tryptophan catabolism may play an important role in preventing inappropriate Th cell responses under normal conditions. However, expansion of Th17 cells that do not induce IDO1-mediated suppression and the reduced capacity of RASF to restrict Th cell proliferation through tryptophan metabolism may support the initiation and propagation of synovitis in RA patients.
Gesehen am 20.09.2018